New technical solutions in technological line for humic fertilizers production - M. A. Gaybaryan; O. V. Ushakov; V. M. Sokololin (Сельскохозяйственные машины и технологии)
The authors considered device and basic principles of technological line operation for complex fertilizers production on a basis of the humic ones. Its technical characteristics, analysis of the received product are given. Relevance of humic fertilizers application in the conditions of modern agriculture is opened. The most perspective of inexpensive organo-mineral fertilizers are humic (humates) and the complex fertilizers created on basis of them. Main active ingredient of such fertilizers are humic and fulvic acids. Humates, making a humus basis, influence structure of the soil well, increasing gas permeability and moisture content, reduce a soil erosion that in many respects determines its yielding potential and fertility. Their application promotes ecological improvement and a detoxication of the polluted lands, recultivation and restoration of the exhausted and infected lands. Humates absorptive radionuclides which are in the soil, pesticides, toxic substances and heavy metals in the insoluble and not acquired by plants connections and therefore provide ecological purity of production. We still have not in Russia industrial production of the specialized equipment for preparation of humic fertilizers from peat. Enterprises have to adapt for these purposes different types of processing equipment borrowed from other industries. However such equipment does not provide a necessary technological mode and reduces quality of fertilizers.